Kinetics and Mechanism of Oxidation of 5-Sulfosalicylic Acid by Ditelluratocuprate(III) in Alkaline Medium - Shan, Jinhuan; ping Liu, Yan (Asian Journal of Chemistry, 2011)
The kinetics of oxidation of 5-sulfosalicylic acid by ditelluratocuprate(III) (DTC) has been studied spectrophotometrically between 283.2 and 303.2 K in alkaline liquids. The reaction rate showed first order dependence in ditelluratocuprate(III) and fractional order in 5-sulfosalicylic acid. It was shown that the pseudo-first order rate constant kobs increased with an increase in concentration of OH– and a decrease in concentration of TeO42-. There is a negative salt effect. A plausible mechanism of reaction involving a pre-equilibrium of adduct formation between the complex and 5-sulfosalicylic acid was proposed. The rate equations derived from mechanism can explain all experimental phenomena. The activation parameters of the rate-determining step have also been computed.